Analisis Dinamika dan Peran Prognostik Neutrophil-Lymphocyte Ratio (NLR) terhadap Derajat Keparahan Infeksi Dengue pada Pasien Pediatrik: Systematic Literature Review 2020–2025 - Rifat Makarim (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Dengue virus infection remains a significant hyperendemic health challenge in Indonesia, where early detection of massive plasma extravasation risk is paramount to reducing mortality rates within the pediatric population. Although routine hematological parameters such as the Neutrophil-Lymphocyte Ratio (NLR) have emerged as applicable prognostic biomarker candidates, existing literature frequently presents contradictory findings. This study analyzes the dynamics and validity of the NLR as a predictor of dengue severity in children through a synthesis of empirical evidence from 2020 to 2025, utilizing a systematic literature review (SLR) following PRISMA protocols. Data synthesis reveals a Biphasic Model explaining NLR fluctuations throughout the disease course; specifically, during the critical phase (days 4–5 of illness), a low NLR (<0.8) consistently serves as a potent independent predictor of Dengue Shock Syndrome (DSS), with an increased risk of up to 39 times due to significant viral-induced myelosuppression. Conversely, in the late shock phase, the NLR tends to rise (>2.0) as a manifestation of adrenergic stress responses or secondary bacterial co-infections. Consequently, the NLR is a valid, cost-effective, and applicable prognostic biomarker for clinical triage, and serial monitoring is highly recommended to distinguish the pre-shock phase from the recovery phase to ensure early optimization of clinical management.